Development and optimization of renewable vinyl plastisol/wood flour composites exposed to ultraviolet radiation. (15th October 2016) - Torres-Giner, S.; Montanes, N.; Fenollar, O.; García-Sanoguera, D.; Balart, R.
Abstract: The application of vegetable oils as novel plasticizers for poly(vinyl chloride) (PVC) is currently in the spotlight of the polymer industry due to their ingrained sustainability. In this study, novel vinyl plastisol/wood flour composites based on epoxidized linseed oil (ELO) were evaluated. For this, PVC was first plasticized by 70 parts by weight of ELO per hundred parts of resin (phr) to form a vinyl plastisol. Wood flour, obtained by dry grinding from reed ( Phragmite communis ), was then incorporated at five different loadings (10, 15, 20, 25, and 30 wt.‐%) and three particle sizes (100, 250, and 500 μm). The effect of ultraviolet (UV) radiation was explored to activate the surface of wood flour to increase its interfacial adhesion with the vinyl plastisol. Stereomicroscopy and scanning electron microscopy (SEM) were used to examine the composites fracture and determine the dispersion of wood flour in the vinyl matrix. As per the surface appearance and mechanical results, optimal materials were observed for vinyl plastisol composites at high contents of wood flour with the largest particles that were previously exposed to UV for 4 min. Resultant renewable vinyl plastisol composites show a great deal of potential as designed materials for wood replacement in building applications. Graphical abstract: Highlights: Renewable vinyl plastisol composites based on epoxidized linseed oil (ELO) were developed by introducing reed wood flour Optimal materials were observed for vinyl plastisol composites containing 20 to 30 wt.-% of wood flour particles of 500 μm Wood flour was exposed to ultraviolet (UV) radiation to increase its interfacial adhesion with the vinyl plastisol Ductility of the vinyl plastisol composites prepared with UV-exposed wood flour for 4 min increased up to 3.5 times.